Dexamethasone in brain tumor patients: a real-world pharmacovigilance audit - Prasad, Vindhya; Elhag, Ali; Onyiriuka, Louis; Mthunzi, Engelbert; Hatch, Sarah; Naeem, Awais; Noureldin, Fatmahelzahraa; Marchi, Francesco; Raslan, Ahmed; Chowdhury, Yasir A.; Shapey, Jonathan; Gullan, Richard; et al. (Frontiers in Neurology, 2025)
IntroductionDexamethasone is routinely prescribed for the management of peritumoral edema in brain tumor patients. Despite available orientations for its management in neuro-oncology patients, the individual needs according to the natural history of the disease and treatment options allied to a hierarchical system with multiple teams involved poses significant challenges in its real-world application.MethodsWe conducted a retrospective single-centre observational study of 316 brain tumor referrals to a tertiary neurosurgical center over a 3-month period. Data was extracted from referral notes, multidisciplinary team (MDT) documentation and clinical records. Steroid-related variables such as indication, dose, duration, weaning plan, complications, and follow-up practices were collected alongside demographic and clinical data.ResultsOf 316 referrals, 210 patients (66.5%) were started on steroids at baseline, yet only 6% had a documented weaning plan at that point. MDT referral occurred in 252 patients (79.7%), where steroid initiation was significantly associated with surgical management (χ2 = 13.1, p < 0.001). However, only 28.8% of MDT-referred patients had a documented steroid plan, with higher rates in surgical patients (41.3%) than those managed conservatively or with best supportive care (BSC) (16.5%, p < 0.001). Steroid-related complications occurred in 11.4% (24/210) of patients, most commonly wound infections. Prolonged steroid use (>2 weeks) (OR = 3.5, [95% CI: 1.1–11.0], p = 0.04), and absence of an MDT steroid plan (OR = 4.2, [95% CI: 1.2–15.0], p = 0.03) were significant predictors of complications, particularly of Common Terminology Criteria for Adverse Events (CTCAE) Grade 2–3 severity. Nurse-led clinic follow-up was more common in surgical patients (91%) than BSC patients (24.6%, p < 0.001) and supported steroid monitoring.DiscussionProlonged steroid use and incomplete documentation of steroid plan were associated with increased steroid-related complications highlighting the need for more robust prescribing protocols and improved multidisciplinary follow-up.